2008
DOI: 10.1107/s0909049508003397
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution X-ray microdiffraction analysis of natural teeth

Abstract: The main component of natural teeth was determined many years ago as calcium phosphate, mostly in the form of hydroxyapatite with different crystallites. In the past, the method used in tooth crystal investigation has been mainly powder X-ray diffraction analysis, but this method has its drawbacks, i.e. the destruction of the natural tooth structure and the difficulty in examining the preferred orientation in different layers of the tooth. During the last century, microzone X-ray diffraction on the tooth surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
40
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 16 publications
9
40
1
Order By: Relevance
“…Therefore, the structure of the enamel is more senestive to γ-radiation than dentin. Similar results were previously reported in the literatures (Xue et al, 2008;Vieira et al, 2003).…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, the structure of the enamel is more senestive to γ-radiation than dentin. Similar results were previously reported in the literatures (Xue et al, 2008;Vieira et al, 2003).…”
Section: Discussionsupporting
confidence: 82%
“…6 ). The results revealed that the average crystal sizes and preferential orientation of the biomimetic coating were almost the same as those of the intact enamel [Xue et al, 2008]. …”
Section: Resultssupporting
confidence: 52%
“…Similar to bones, the inorganic part of teeth also consist of biological apatite (Xue et al 2008). The stability of the mineral composition of teeth also has a very long history: namely, CaPO 4 were found in fossil fish teeth (Gaft et al 1996).…”
Section: Teethmentioning
confidence: 99%